PENGARUH MASA KERJA TERHADAP KANDUNGAN Pb (PLUMBUM) DALAM DARAH SOPIR ANGKUTAN KOTA KUPANG TAHUN 2009 - OLGA MARIANA DUKABAIN; DEBORA GAUDENSIANA SULUH (JURNAL INFO KESEHATAN, 2013)
Pb (lead) is a highly toxic heavy metals and obtained from consuming food, beverages or through inhalation (breathing) from the air, lead-contaminated dust and contact through the skin. The effects of Pb may occur in the City which is a transport driver vulnerable workers exposed to lead because of the daily work that is always associated with motor vehicles. This research is an analytical survey which is aimed to determine the effect ofworking period to the content of Pb in blood transport driver in Kupang in 2009. The population in this study is all the Kupang public transportation drivers in 2010 with a total sample of 15 drivers, who divided his working period in three categories: <1 year, 1-5 years and> 5 years. Laboratory data and then tabulated and analyzed statistically using linear regression are used to determine the effect of working period to the content of Pb in blood of public transport drivers. Results of laboratory examinations of 15 people found that the public transportation drivers have different Pb content and where on working period with the category of <1 year average content of Pb in blood was 0,89 mg/ltr, 1-5 years category average content of Pb is 1,26 mg / l and media> five-year average content of Pb is 1,99 mg/l. Results-t test and regression analysis showed that the variable (X) has a t-count equal to 3.912, while the value of the t-table with df = 13 at α = 0.01 amounted to 3.012. Thus an individual variable (X) significantly affect the variabels in blood Pb (Y). Based on the analysis results can be concluded that the longer working period as a transport driver in the city of Kupang, the higher content of Pb in blood, and vice versa if the working period is reduced or the less will reduce the content of Pb in blood.